Carlos Ghosn: The rise and fall of an automobile legend (B) - REB, Jochen (Institutional Knowledge at Singapore Management University, 2020)
Carlos Ghosn, a Brazilian-Lebanese-French, is by many counts, one of the – if not the – most celebrated automotive executives of the late 20th and early 21st century. This is a two-part case about his career, leadership, and decision-making. Part A starts in 1999, the early days of Ghosn’s arrival in Japan, where he went on a mission to rescue Nissan, one of the biggest Japanese car manufacturers with a long tradition that had run into trouble and was in danger of bankruptcy. Ghosn went there after Renault entered into an alliance with Nissan in 1999. The case then goes back in time, following Ghosn from when he was born in Brazil, and then moved to Lebanon and later France, where he studied and began his career at Michelin. The case ends in November 2018, with talk about the potential merger of Renault and Nissan into a single company having stalled, leaving the alliance in status quo. Part A of the case is structured around a key tension: What happens when the cosmopolitan, melting-pot, aggressive Ghosn – who made his name as ‘le cost-killer’ – meets corporate Japan, with its very homogenous, indirect, and conflict-avoiding culture? Part B starts on November 19, 2018, when Carlos Ghosn is arrested as he arrives at Haneda Airport in Tokyo, Japan. The accusations against him include allegations of misappropriation of company funds for personal use and concealment of a large amount of remuneration. According to the chief prosecutor, Ghosn’s wrongdoings were more serious than insider trading. The case presents in some detail the different allegations against Ghosn, and then describes the reactions of Ghosn and Nissan to the accusations. It ends with a recounting of some of the subsequent events, including the granting of bail to Ghosn. Part B of the case is meant to facilitate discussion around a key question: How could someone as successful as Ghosn have come to engage in the kinds of behaviours he was accused of? The case’s key tension provides a wonderful opportunity for students to reflect and discuss issues around culture, leadership, (un)ethical decision-making and behaviour in general, as well as in organisational contexts. Through this case, students will be able to learn about national and corporate culture, cross-cultural management and communication, decision-making style, governance, ethics in leadership, bounded rationality, self-motivated reasoning and self-serving biases.